Oxidative stress involved in textural changes of sea cucumber Stichopus japonicus body wall during low-temperature treatment. Issue 1 (1st January 2018) - Dong, Xiufang; Qi, Hang; Feng, Dingding; He, Baoyu; Nakamura, Yoshimasa; Yu, Chenxu; Zhu, Beiwei
ABSTRACT: It is difficult to maintain the high quality of sea cucumber Stichopus japonicus ( S. japonicus ) during regular thermal processing due to the special physiochemical makeup of S. japonicus body wall (SJBW) that affects its textural properties. Hence, it is very necessary to understand the parameters controlled textural alteration and the potential mechanisms during thermal processing of SJBW. In the present study, morphology, hardness and chewiness of SJBW gradually changed starting from 3 h during thermal processing. SDS-PAGE analysis indicated that notable proteolysis occurred in actin and other proteins with molecular weight of 200 kDa in a time-dependent manner. DNA fragmentation, cathepsin L and caspase-3-like activities also increased in SJBW. Within 1 h of incubation, both phosphorylated p38 and c-jun N-terminal kinase (JNK) and reactive oxygen species (ROS) production in SJBW reached the highest levels, and then returned back to the original levels after 3 h. A plausible signaling pathway in SJBW during low-temperature treatment is as follows: ROS produced, Mitogen-activated protein kinases (MAPK) phosphorylation, endogenous enzyme activation, DNA damage, protein degradation, and textural tenderization. Understanding the molecular mechanism underlying physiochemical changes during low-temperature treatment would be essential to achieve better control of the texture and quality of SJBW.